2010
DOI: 10.1016/j.jeem.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Environmental policy à la carte: Letting firms choose their regulation

Abstract: a b s t r a c tUnder uncertainty, the optimal choice between price and quantity instruments depends on the technology of the regulated firms, which is often private information. We consider an environmental policy that delegates the prices-versus-quantities decision to the firms by offering them the choice between an emissions tax and permit trading. Such an approach is currently used in Swiss climate policy. We provide a detailed characterization of the optimal policy and show that this approach reduces expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 21 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The use of a mix of policy instruments in a static sense is widely reported in the literature (e.g. Roberts and Spence 1976;Pizer 2002;Liao 2007;Krysiak and Oberauner 2010;also Shobe et al 2014 write about a 'hybrid approach' implemented in California), but an inter-temporal mix, or an inter-temporal hybrid of an emissions tax and a tradable permit scheme has not yet been investigated in detail. This represents an important gap in our understanding of how the combination of two or more policy instruments over time could deliver improved outcomes in terms of lower cost GHG emissions abatement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a mix of policy instruments in a static sense is widely reported in the literature (e.g. Roberts and Spence 1976;Pizer 2002;Liao 2007;Krysiak and Oberauner 2010;also Shobe et al 2014 write about a 'hybrid approach' implemented in California), but an inter-temporal mix, or an inter-temporal hybrid of an emissions tax and a tradable permit scheme has not yet been investigated in detail. This represents an important gap in our understanding of how the combination of two or more policy instruments over time could deliver improved outcomes in terms of lower cost GHG emissions abatement.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a mix of policy instruments in a static sense is widely known in the literature (e.g., Roberts and Spence, 1976;Pizer, 2002;Krysiak and Oberauner, 2010;also Shobe et al, 2014 write about a 'hybrid approach' implemented in California), but the inter-temporal mix, or an inter-temporal hybrid of an emissions tax and a tradable permit scheme has not yet been investigated in detail. As far as the authors are aware, this is the first study that explicitly examines this type of inter-temporally hybridized policy design, in which a tradable permit scheme sequentially follows an emissions tax.…”
Section: Introductionmentioning
confidence: 99%
“…Even though economists typically prescribe the use of a (single) Pigovian tax on emissions in order to internalize climate-related emission externalities, almost all countries use a range of instruments such that firms are subject to more than one emissions policy. This is usually viewed as problematic (see, e.g., Fankhauser et al, 2010), but it could be justified by market failures in addition to the climate externality (Fischer and Preonas, 2010), uncertainty about the future climate policy (Lecuyer and Quirion, 2013) or private information (Krysiak and Oberauner, 2010). Overlapping instruments are usually explained using political-economy considerations (Jenkins, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The 'prices versus quantity' literature has found that reducing emissions through price control is preferable to quantity control if marginal costs are steeper compared to marginal benefits (Weitzman, 1974;Nordhaus, 1994;Newell & Pizer, 2003); that this holds under a wide range of circumstances (Kolstad, 1996;Hoel & Karp, 2002;Quirion, 2004;Pezzey & Jotzo, 2012); and that hybrid schemes of prices and quantities can reduce costs associated with uncertainty about benefits and costs (Roberts & Spence, 1976;Mandell, 2008), address problems of asymmetric information (Krysiak & Oberauner, 2010), and contribute to cost containment (Pizer, 2002). This literature pivots around the relationship between the marginal cost and marginal benefit of the provision of a public good under uncertainty.…”
Section: Introductionmentioning
confidence: 99%